Resistência à fratura, grau de conversão, adaptação marginal e contração de polimerização de uma resina composta bulk-fill - Jassé, Fernanda Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to evaluate different properties of a low-shrinkage stress bulk-fill flow composite resin, through three studies: 1) evaluation of the fracture strength of molars with Class II MOD cavities restored with the bulk-fill resin; 2) evaluation of degree of conversion (DC%) by means of FTIR (Fourier Transform Infrared) spectroscopy; and 3) evaluation of cervical marginal adaptation in enamel and dentin, and polymerization shrinkage. For the study of fracture strength, 40 molars were divided into five groups: 1- intact teeth (positive control); 2- teeth with Class II MOD cavities without restoration (negative control); 3- teeth with Class II MOD cavities restored with only bulk-fill resin; 4- teeth with Class II MOD cavities restored with bulk-fill resin covered with conventional nano-hybrid resin; and 5- teeth with Class II MOD cavities restored with only the conventional nano-hybrid resin. All specimens were subjected to fracture strength test by means of axial compressive load, using a metal sphere measuring 8 mm in diameter, in an universal testing machine EMIC DL-2000 equipped with 10 kN load cell, which was triggered at a speed of 5 mm/min until the fracture of the specimen. Data of fracture resistance were subjected to Analysis of Variance (ANOVA) and Tukey's test (! = 0.05). To analyze DC% cylindrical specimens (4mm x 4mm) of the resin were made and divided into the depths of polymerization of 1mm, 2mm, 3mm and 4mm. The specimens were photo-activated by the times of 20 and 40 seconds, and then they were crushed, pressed with KBr (potassium bromide) and analyzed by FTIR spectrophotometer. Data for DC% were statistically analyzed by two-way ANOVA. For the third study, which evaluated the cervical marginal adaptation and polymerization shrinkage, at first, 24 molars were divided into three groups (A, B and C) ... (Complete abstract electronic access below)

O objetivo neste trabalho foi avaliar diferentes propriedades de uma resina composta bulk-fill fluida de baixo tensão de contração, por meio de três estudos: 1) avaliação da resistência à fratura de molares com cavidades classe II MOD restaurados com a resina bulk-fill; 2) avaliação do grau de conversão monomérica (GC%) por meio de espectroscopia FTIR (Espectroscopia Infravermelho Transformada de Fourier); e 3) avaliação da adaptação marginal cervical em esmalte e dentina, e da contração de polimerização. Para o estudo de resistência à fratura, 40 molares foram divididos em cinco grupos: 1- dentes hígidos (controle positivo); 2- dentes com cavidades classe II MOD sem restauração (controle negativo); 3- dentes com cavidades classe II MOD restaurados apenas com a resina bulk-fill; 4- dentes com cavidades classe II MOD restaurados com a resina bulk-fill recoberta por resina composta convencional nano-híbrida; e 5- dentes com cavidades classe II MOD restaurados apenas com a resina convencional nano-híbrida. Todos os espécimes foram submetidos ao teste de resistência à fratura por meio de carga compressiva axial, com o emprego de esfera metálica medindo 8 mm de diâmetro, em máquina de ensaio universal EMIC DL-2000, equipada com célula de carga de 10 kN, acionada a uma velocidade de 5 mm/min até que ocorresse a fratura do conjunto. Os dados de resistência à fratura foram submetidos à Análise de Variância (ANOVA) e teste de Tukey (! = 0,05). Para análise do grau de conversão foram confeccionados espécimes cilíndricos (4mm x 4mm) da resina, divididos nas profundidades de polimerização de 1mm, 2mm, 3mm e 4mm. Os espécimes foram foto-ativados pelos tempos de 20 e 40 segundos, e foram então triturados, prensados com KBr e analisados em espectrofotômetro FTIR. Os dados relativos ao GC% foram analisados estatisticamente... (Resumo completo, clicar acesso eletrônico abaixo)
Fracture strength, degree of conversion, marginal adaptation and polymerization shrinkage of a bulk-fill resin composite
Keywords: Força compressiva; Adaptação marginal dentária; Resinas compostas; Fourier, Espectroscopia de infravermelho por transformada de; Polimerização